Methodologies for the evaluation of social projects in rural areas (Revista de Investigaciones Universidad del Quindío, 2022)
The purpose of this article is to investigate the different methodologies for the evaluation of social projects at the international and local levels, based on this, to propose new or combined practices for the evaluation of social projects in rural areas. With this research it was observed that the importance given to the evaluation of social projects has been very little, and mostly invulnerable populations. In general, there is no culture of accountability that helps to make decisions based on experiences and, in addition, the review of the articles studied shows that sometimes the projects do not generate the expected effects or may even have negative impacts on the population and the environment in which they intervene.  This article is composed of the introduction where the purpose of the research is presented, the methodology used, the discussion in which the different methodologies applied in the evaluation of projects are reviewed, the results where a way to evaluate social projects in rural areas is presented, and finally, the conclusion where a general reflection of what was found in the article and recommendations for future research are given.
Keywords: Ex-post evaluation; social projects; project evaluation; impact; zones rural